The Effects of Anesthesia, Mouse Strain, and Age on Intraocular Pressure and an Improved Murine Model of Experimental Glaucoma - Cone, Frances E. (2012)
The purpose of this study was to improve a mouse model of chronic intraocular pressure (IOP) elevation utilizing microbead injection in two strains of mice and to assess the effect of age and anesthesia on measured IOP. We compared our previous model with two modified protocols for injecting polystyrene microbeads and viscoelastic material in CD1 or C57BL/6 mice. The measured outcomes were degree of IOP elevation and production of axonal loss. The first new protocol was injection of 3µL of equal volumes of 6µm and 1µm diameter beads, followed by 2µL of viscoelastic (3+2). The second new protocol injected 4µL of the two bead mixture, then 1µL of viscoelastic (4+1). Both were compared to injection of 2µL of 6µm beads with 3µL of viscoelastic (2+3). We also compared the effects of age and of two anesthetic regimens (intraperitoneal ketamine/xylazine/acepromazine versus isoflurane gas) on measured IOP in untreated eyes of both strains. IOP was 2 mm Hg lower with intraperitoneal than with gas anesthesia in both strains (p=0.003, p<0.0001, t-test). IOP measurements were lower in untreated young (2 months) compared to older (10 months) C57BL/6 mice (p=0.001, t-test). In the experimental glaucoma mouse model, mean IOP and number of elevated IOP measurements were higher in newer protocols. Mean axon loss with the 4+1 protocol (all strains) was twice that of the 2+3 and 3+2 protocols (36% vs. 15% loss, p = 0.0026, ANOVA), and mean axon loss in CD1 mice (21%) was greater than in C57BL/6 mice (13%) (p = 0.047, ANOVA). Median axon loss in 4+1 protocol treated C57BL/6 mice expressing yellow fluorescent protein in 2% of retinal ganglion cells (RGCs) had greater median axon loss than C57BL/6 4+1 protocol treated mice (26% vs. 10%, p=0.03). The 4+1 protocol provided higher, more consistent IOP elevation and greater axonal loss. The effects of age, strain, and anesthesia on induced IOP elevation and axon damage must be considered in mouse experimental glaucoma research.